2015
DOI: 10.1080/15476286.2015.1017231
|View full text |Cite
|
Sign up to set email alerts
|

Translation attenuation via 3′ terminal codon usage in bovinecsn1s2is responsible for the difference in αs2- and β-casein profile in milk

Abstract: The rate of secretion of αs2-casein into bovine milk is approximately 25% of that of β-casein, yet mammary expression of their respective mRNA transcripts (csn1s2 and csn2) is not different. Our objective was to identify molecular mechanisms that explain the difference in translation efficiency between csn1s2 and csn2. Cell-free translational efficiency of csn2 was 5 times that of csn1s2. Transcripts of csn1s2 distributed into heavier polysomes than csn2 transcripts, indicating an attenuation of elongation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, although LH3.0 increased the phosphorylation of eEF2 and LT1.3 increased the mRNA expression of eEF2, no differences were detected at the transcriptional or translational levels. The differences in the regulation may be attributable to different translation efficiencies and posttranscriptional modifications of the same gene-for example, effects due to the GC content, secondary structure, 5′ and 3′ untranslated regions, codon usage efficiencies, and protein binding sites that influence ribosome recruitment and transit (Kim et al, 2015). In addition, the downregulation of EEF2 following the OPAA treatment compared with the control indicated that eEF2 could be modulated by AA in an mTOR-dependent manner (Appuhamy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although LH3.0 increased the phosphorylation of eEF2 and LT1.3 increased the mRNA expression of eEF2, no differences were detected at the transcriptional or translational levels. The differences in the regulation may be attributable to different translation efficiencies and posttranscriptional modifications of the same gene-for example, effects due to the GC content, secondary structure, 5′ and 3′ untranslated regions, codon usage efficiencies, and protein binding sites that influence ribosome recruitment and transit (Kim et al, 2015). In addition, the downregulation of EEF2 following the OPAA treatment compared with the control indicated that eEF2 could be modulated by AA in an mTOR-dependent manner (Appuhamy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the bovine species, Kim et al . (2015) show that the usage of the last 28 codons of CSN1S2 is the main regulatory element attenuating its expression, and it is responsible for the differential translational expression of the CSN1S2 and CSN2 . In particular, the authors reported that the codon usage and order influenced the accuracy and the speed of translation.…”
Section: Resultsmentioning
confidence: 99%
“…Analogously, in donkey lactating mammary gland the CSN2 and CSN1S2 I transcripts represent respectively 70.85 and 14.23% of the total casein mRNAs, while the corresponding protein concentration is 54.28 and 7.19% respectively, with a greater CSN2 translation efficiency of about 1.5 times. In the bovine species, Kim et al (2015) show that the usage of the last 28 codons of CSN1S2 is the main regulatory element attenuating its expression, and it is responsible for the differential translational expression of the CSN1S2 and CSN2. In particular, the authors reported that the codon usage and order influenced the accuracy and the speed of translation.…”
Section: Csn3mentioning
confidence: 99%
“…The proportion of αs2-CN in milk changes considerably between species and is absent from human and marsupial milk (Kim et al, 2015 ). In buffalo milk, the αs2-CN is the third most abundant casein fraction (4.99 g/L), and the corresponding coding gene ( CSN1S2 ) showed a lower translation efficiency (0.25) compared to the other casein genes as CSN3 (k-CN, 2.69), CSN2 (β-CN, 2.39), and CSN1S1 (αs1-CN, 1.31) (Cosenza et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%